Biotransformation of alisol G by Penicillium janthinellum and the hCE2 inhibitory effects of its metabolites. (September 2015) - Mai, Zhen-Peng; Xin, Xiu-Lan; Sun, Zheng; Zhang, Ning; Huang, Shan-Shan; Wang, Chao; Chen, Liang; Li, Ye; Huo, Xiao-Kui; Fan, Guang-Jun
Graphical abstract: Microbial transformation of alisol G by Penicillium janthinellum AS 3.510 resulted in the production of metabolites1 –4 with new strucutres. Highlights: Microbial transformation of alisol G by Penicillium janthinellum AS 3.510 yielded metabolites1 –4 . Metabolites1 –4 were identified to be new compounds by spectroscopic analyses. In an in vitro bioassay, metabolites1 –4 showed significant hCE2 inhibitory activities. Abstract: Alisol G, also named 25-anhydroalisol A, is a major triterpene obtained from dried rhizomes of Alisma orientalis . This paper investigated the transformation of alisol G by fungi and evaluated the hCE2 inhibitory effects of the transformed products. By screening whole cells of 10 strains of filamentous fungi, Penicillium janthinellum AS 3.510 exhibited a special capability to transform alisol G. Four metabolites were obtained, which were determined to be new compounds on the basis of spectroscopic data, including UV, 1D- and 2D-NMR, and HRESIMS. In addition, in an in vitro bioassay, metabolites1 –4 showed significant hCE2 inhibitory activities with IC50 values of 6.81, 16.66, 3.38, and 6.33 μM, respectively.